QssB: a pleiotropic RNPP-type cell-cell communication system in C. acetobutylicum ATCC 824 - Severn, Oliver (2018)
Clostridium acetobutylicum is renowned for the ability to convert sugars into acids and solvents, including the potential biofuel butanol. However, regulation of its fermentation metabolism remains poorly understood, especially regarding the shift from acid to solvent metabolism. Several RNPP-type cell-cell communication systems have recently been discovered within C. acetobutylicum ATCC 824. The aim of this study was to investigate one such system, Quorum Sensing System B (QssB), consisting of a regulator, QsrB, and a signalling peptide of unknown structure derived from a precursor protein, QspB. The primary objectives were to characterise this system in greater detail, its effects on metabolism and endospore formation, and to gain insights into the nature of the signalling process. Overexpression of qsrB confirmed a dramatic reduction of solvent production and sporulation, and revealed increased production of acetate and butyrate, with considerably decreased consumption of glucose. These phenotypes were overcome by the addition of synthetically produced peptides matching the C-terminal region of the conjugate signalling peptide QspB. In doing so, the minimum peptide sequence required to relieve the effects of qsrB overexpression was shown to be the heptamer AEPTWGW. The system was shown to be highly selective for this sequence, with an alanine scan showing the sequential reduction in biological activity. QssB did not engage in cross talk with the other RNPP-type systems present within the organism, or with a homologous system discovered in Clostridium roseum, further evidence of selectivity. Attempts were made to identify the Specific Binding Protein (SBP) required for QspB uptake via ABC transport. ClosTron mutation of two SBP encoding genes, CA_0176 and CA_C3632, conferred resistance to the effects of QsrB overproduction on sporulation. An iTRAQ-based proteomics approach was used to study the wider effects of qsrB overexpression, as well as their alleviation via synthetic peptide. This analysis confirmed that the qsrB overexpressing strain remained in an acidogenic state which could be overcome though peptide addition. Although glucose consumption was decreased upon QsrB overproduction, key glycolysis enzymes were found to be upregulated. The stationary phase regulator CA_C0957 was found to be downregulated under these conditions, whereas proteins associated with motility and chemotaxis increased in abundance. GusA reporter assays supported the former, whilst swimming and swarming assays remained inconclusive. Enzyme assays revealed increased acetate and butyrate kinase activity, agreeing with the acidogenic state suggested from the iTRAQ analysis. QsrB was confirmed to be a repressor of solvent production and the production of endospores, with new evidence indicating further complexity.